(untitled) (Comprehensive Journal of Science, 2026)
This study analyzes the contemporary counseling needs of students in gifted centers in Libya during 2015–2025 through a critical review of Arabic and international literature and relevant psychological and educational theories, Using an analytical narrative review approach, it examines the educational, psychological, and social dimensions of gifted students’ needs in light of Maslow’s, McClelland’s, Murray’s, and Albert Ellis’s theoretical perspectives and their implications for the Libyan context. Findings show that gifted learners have complex counseling needs extending beyond academics، Educationally, they require enrichment curricula, structured acceleration, and instruction that promotes higher-order thinking, Psychologically, they face pressures related to perfectionism, anxiety, and high expectations, requiring support that strengthens well-being and self-esteem, Socially, some experience isolation and belonging difficulties, highlighting the need for supportive peer environments. The study concludes that the effectiveness of gifted centers depends on integrated counseling systems and identifies gaps in applied research and specialized services in Libya, it recommends strengthening counseling provision, training specialists, and fostering safe learning environments to support balanced and sustainable development.